Antera 3D camera: A novel method for evaluating the therapeutic efficacy of fractional CO2 laser for surgical incision scars. (6th August 2018) - Zhang, Nan; Shi, Kai; Hong, Lei; Zhao, Jingchun; Yu, Jiaao
Summary: Objective: To introduce a novel method for evaluating the therapeutic efficacy of fractional CO2 laser for incision scars. Methods: A total of 72 patients after incision healing for at least 2 years were included in the series, with scars on neck, thyroid, chest, and limb from September 2013 to September 2016. The image of scar was taken by Antrea 3D camera before the treatment, VSS, and UN4P were also applied for scar evaluation. A total of four sessions at 4‐6 intervals were conducted to each patient. After 3 months of last session, a final assessment was carried out by Antera 3D and VSS, UN4P independently. Results: The Antera scores for color after 4 sessions were 8.78 ± 2.11, which were significantly lower than the prior treatment (9.62 ± 1.90, t  = 2.51, P  < 0.05). The Antera scores for texture after four sessions were 22.80 ± 5.23, which was significantly lower than the prior treatment (30.33 ± 5.41, t  = 8.48, P  < 0.05). The Antera scores for melanin levels after four sessions were 0.52 ± 0.05, which was significantly lower than the prior treatment (0.54 ± 0.05, t  = 2.4, P  < 0.05). The Antera scores for hemoglobin levels after four sessions were 1.88 ± 0.50, which was significantly lower than the prior treatment (2.11 ± 0.45, t  = 2.90, P  < 0.05). The Vancouver Scar scores after four sessions were 7.1 ± 2.0, which showed no statistically significant differences with the prior treatment (7.5 ± 2.4, t  = 1.09, P  = 0.25 > 0.05). The University of North Carolina "4P" Scar scores after four sessions were 6.6 ± 1.5, which also showed no statistically significant differences with the prior treatment (7.0 ± 1.9, t  = 1.40, P  = 0.15 > 0.05). Conclusions: For scar therapeutic evaluation, Antera 3D camera is objective and accurate, and is worthy of wide promotion.